THE SHANGHAI COOPERATION ORGANIZATION AND REGIONAL SECURITY PROBLEMS - AKMALOV, Shoislam (CENTRAL ASIA AND THE CAUCASUS, 2005)
Today Central Asia is one of the most unique regions of the world, since it has several institutional formations in which essentially all of its countries participate. This phenomenon appears to be spurred on not only by the dynamics of the processes occurring in these states and throughout the region as a whole, but also in the area around it. One of the largest regional structures in Central Asia is the Shanghai Cooperation Organization (SCO). The sum territory of its member states covers more than 30 million sq. km of the Eurasian continent, thus ensuring them geostrategic access to Europe in the West and the Asia Pacific Region in the East. In so doing, the total number of residents of the SCO countries is close to 1.455 billion (approximately 25% of the planet’s entire population). 1 The status of Russia and China as permanent members of the U.N. Security Council has significantly raised the political potential of this organization in resolving the key problems of international and regional security. An important stage in the development of the Shanghai Cooperation Organization was the Tashkent summit held on 16-17 June 2004. It marked the end of the institutional formation of the SCO: in 2002, its Charter was adopted, in 2003, a permanent secretariat was instituted in Beijing, and in 2004, the Regional Antiterrorist Structure (RATS) was formed, the general headquarters of which is in Tashkent. The Central Asian countries view the SCO as an effective forum for mutual dialog. The opening of RATS in Tashkent is also in keeping with the U.S.’s interests, since Washington supports any form of opposition to terrorism, and the fact that RATS is located in Tashkent indicates Uzbekistan’s active participation in this sphere. 2